INFORMATIONAL ROLE OF FINANCIAL STATEMENT INDICATORS IN THE ENTERPRISE MANAGEMENT SYSTEM (INNOVATIVE ECONOMY, 2022)
Shnurko A.M., Martynenko O.V., Holovko S.O. INFORMATIONAL ROLE OF FINANCIAL STATEMENT INDICATORS IN THE ENTERPRISE MANAGEMENT SYSTEMPurpose.The aim of the article is to research the information needs of different groups of users, clarify the terminological interpretation of the definition of “financial reporting”, as well as determination of the informational role of indicators of financial reporting of the enterprise in the conditions of constant changes in legislation.Methodology of research. Theoretical and methodological basis of the study were scientific methods of cognition, based on a systematic approach to determining the informational role of financial reporting indicators in the enterprise management system. A number of general and special scientific research methods were used to achieve this goal and obtain the results of the study: dialectical; monographic (when processing scientific publications); system analysis (in the study of the informational role of financial reporting indicators in the enterprise management system); method of analogies and comparisons (in the study of the legal framework); comprehensive analysis (when forming conclusions and proposals for solving the tasks) and others.Findings. Based on the analysis of theoretical and methodological approaches, the essence of the terminological interpretation of the definition of “financial reporting” is revealed. According to the results of the study, approaches to the interpretation of the concept of “financial reporting” are systematized. Consumer groups (internal and external), interests and sources of information of financial reporting indicators are identified. The requirements of users to the qualitative informative characteristics of the forms of financial reporting are revealed. Among them are: profitability, relevance, reliability, comparability, materiality and their essence.Logically interconnected parts of in formativeness of reporting indicators are determined: the first - performance indicators for assessing the effectiveness of the enterprise for the relevant period, which are in some way grouped and summarized in the forms of financial statements; second - basic information that provides an understanding of the indicators of the main forms of financial reporting and includes a description of the conceptual principles and principles of accounting policy, information about the industry, type of enterprise, its management, business concept, development strategy.Originality. The study of the informational role of financial reporting indicators in the enterprise management system at the present stage of management has been further developed.Practical value. These proposals for the adoption of additional measures at the legislative level to regulate the process of revaluation and depreciation of current and non-current assets will make it impossible to create conditions for the manipulation of financial statements.Key words: indicators of financial reporting; users of financial reporting; enterprise management; forms of financial reporting.
Keywords: indicators of financial reporting; users of financial reporting; enterprise management; forms of financial reporting.